2007
DOI: 10.1111/j.1365-2893.2007.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interferon plus ribavirin in the treatment of hepatitis C virus genotype 5

Abstract: Hepatitis C virus (HCV) genotype 5 has only been reported in a few countries and treatment response has not been well characterized. Our aim is to present the treatment outcome for HCV genotype 5 patients evaluated at three medical centres in Syria between January 2004 and June 2007. Medical records were reviewed retrospectively. Treatment consisted of ribavirin 1 000-1 200 mg daily plus interferon alpha-2a, 3 MU x 3/week or pegylated-interferon alpha-2a, 180 mug/week. Patients were treated for 24 or 48 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…Antaki and colleagues have published a retrospective study of genotype 5 infected patients treated with PEG-IFN/RBV. By this retrospective analysis, genotype 5 infected patients have an SVR rate of 67% [58], exactly as our tree predicts.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Antaki and colleagues have published a retrospective study of genotype 5 infected patients treated with PEG-IFN/RBV. By this retrospective analysis, genotype 5 infected patients have an SVR rate of 67% [58], exactly as our tree predicts.…”
Section: Resultssupporting
confidence: 79%
“…Such a correlation suggests the intriguing forecast that prospective clinical trials for genotypes 5 and 6 will show intermediate response rates, between genotypes 4 and 2, to interferon-based regimens. This prediction is notably in line with current retrospective data regarding the SVR for genotype 5 [58]. It also highlights the need for more molecular studies that explore the genotype-specificity of HCV-immune interactions.…”
Section: Discussionsupporting
confidence: 83%
“…Patients with genotype 5a have been shown to respond better to pegylated-IFN and ribavirin therapy when compared to genotypes 1a and 1b, with response rates ranging from 48% to 67% (D'Heygere et al, 2011;Antaki et al,2008, Legrand-Abravanel et al, 2004, Bonny et al, 2006, Prabdial-Sing et al, 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The standard of care (SOC) for treating hepatitis C in South Africa is combination therapy with pegylated interferon (PEG-IFN) and ribavirin (Botha et al, 2010). Individuals with genotype 5a, the predominant genotype in South Africa, have response rates to combination therapy ranging from 47-67% (Antaki et al, 2008;Devaki et al, 2015). However, many South Africans: typically present with advanced diseases for them to benefit from therapy, have poor access or cannot afford the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8 Antaki et al reported data suggesting that a 24 week course of pegylated interferon and ribavirin could suffice for infected patients with HCV genotype 5. 9 These data might suggest that HCV genotype 5 is intrinsically sensitive to the current antiviral treatment.…”
Section: Introductionmentioning
confidence: 99%